HADIS-HADIS TENTANG METODE KOMUNIKASI RASULULLAH DENGAN SAHABAT - Ritonga, Elfi Yanti (Jurnal Ilmiah Al-Hadi, 2019)
The Messenger of Allah in conveying treatises to Muslims and to believers namely his companions. Communicating with the companions of the Prophet in delivering preaching there are times with the methods of informative communication, persuasive communication and instructive communication.Informative Communication is communication that is informative, often also called speeking informativ. This method is the same as a teacher teaching students or an expert giving a public lecture. Persuasive Communication is communication that aims to change or influence one's beliefs, attitudes, and behaviors so that they act according to what is expected by the communicator. Coersive/Instructive Communication is a communication method that is oppressive, coercive and instruction. The three methods of communicating the Messenger of Allah with friends will be connected with several traditions by discussing the traditions of the Hadith, criticism of Sanad, criticism of devil, and fiqh of al-hadith.